CBMT-32. IMAGING A HALLMARK OF CANCER: TERT EXPRESSION LEADS TO MRS-DETECTABLE METABOLIC REPROGRAMMING. (5th November 2018) - Viswanath, Pavithra; Pieper, Russell; Ronen, Sabrina
Abstract: Hotspot promoter mutations reactivate expression of telomerase reverse transcriptase ( TERT ) in mutant IDH1 oligodendrogliomas. TERT expression allows glioma cells to avoid telomere dysfunction-induced senescence, thereby enabling limitless proliferation. Since TERT expression is essential for glioma proliferation and TERT inhibitors are attractive therapeutic targets, identification of metabolic biomarkers of TERT expression will facilitate non-invasive imaging of tumor status and response to therapy. Therefore, the goal of this study was to identify 1 H- and hyperpolarized 13 C-magnetic resonance spectroscopy (MRS)-detectable metabolic biomarkers of TERT expression in mutant IDH1 glioma cells. We studied mutant IDH1-expressing immortalized normal human astrocytes without (NHApre ) and with TERT expression (NHApost and NHAtert ). Using 1 H-MRS we monitored steady-state metabolite levels and analyzed the data in an unbiased manner using principal component analysis. Our results indicated that the metabolic profile of NHApre cells differed significantly from that of NHApost and NHAtert . Elevated levels of glutathione (GSH, reduced), NADPH, NADH, aspartate and taurine in NHApost and NHAtert cells relative to NHApre were responsible for this discrimination. These results identify 1 H-MRS-detectable biomarkers of TERT expression in mutant IDH1 glioma cells. Next, we used 13 C-MRS to examine [2- 13 C]-glucose flux to the pentose phosphate pathway (PPP) since the PPP is a major source of NADPH, which, in turn, maintains GSH levels. PPP fractional flux was significantly higher in NHApost and NHAtert cells relative to NHApre, consistent with higher levels of NADPH and GSH in the TERT-expressing models. Importantly, the flux of hyperpolarized [U- 13 C]-glucose to the PPP intermediate 6-phosphogluconate was elevated in NHApost and NHAtert cells relative to NHApre, thereby identifying hyperpolarized [U- 13 C]-glucose as a potential imaging biomarker of TERT status. Collectively, our study links TERT expression to significant metabolic reprogramming in mutant IDH1 gliomas and identifies 1 H- and hyperpolarized 13 C-MRS biomarkers that may be valuable for monitoring tumor TERT status and response to therapy.